2018
DOI: 10.1159/000489384
|View full text |Cite
|
Sign up to set email alerts
|

Intravenously Delivered Allogeneic Mesenchymal Stem Cells Bidirectionally Regulate Inflammation and Induce Neurotrophic Effects in Distal Middle Cerebral Artery Occlusion Rats Within the First 7 Days After Stroke

Abstract: Background/Aims: Neurotrophic effects and immunosuppression are the main therapeutic mechanisms of mesenchymal stem cells (MSCs) in stroke treatment. Neurotrophins are produced by graft cells, host neurons, astrocytes, and even microglia/macrophages. Meanwhile, MSCs can increase inflammation if they are not sufficiently induced by pro-inflammatory cytokines. We examined whether intravenously transplanted bone marrow MSCs (BM-MSCs) increase inflammation in distal middle cerebral artery occlusion (dMCAO) rats, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…Grid walking test was used to measure motor coordination deficits after ischemic stroke for each group . The mice were placed on an elevated square grid with each grid cell being 1.5 × 1.5 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Grid walking test was used to measure motor coordination deficits after ischemic stroke for each group . The mice were placed on an elevated square grid with each grid cell being 1.5 × 1.5 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In brief, primary cultures of bone marrow stromal cells were obtained from donor young adult male rats, and BMSCs were isolated as previously described [ 15 , 19 ]. Animals were anesthetized with 3.5% isoflurane and then maintained with 1.0–2.0% isoflurane in N 2 O : O 2 (2 : 1).…”
Section: Methodsmentioning
confidence: 99%
“…By using immunostaining, we found that IGF-1 signals are mainly located in the infarct area. A minority of IGF-1 signals colocalize with NeuN+ neurons and CD68+-activated microglia in infarcts; nonetheless, quantitative analysis showed that these cells cannot account for all of the IGF-1-positive signals [ 15 ]. Other contributors in the brain and periphery (IGF-1 can cross the blood-brain barrier (BBB) [ 16 18 ]) to the increased IGF-1 signals in the brain warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Grid walking test was used to measure motor coordination deficits after ischemic stroke for each group [30]. The mice were placed on an elevated square grid with each grid cell 1.5X1.5 cm 2 .…”
Section: Grid Walking Testmentioning
confidence: 99%